A Coolie Bell. All gold. Trinidad B.W.I. [sic] - (:unkn) unknown (My University, 2008)
East Indian woman in traditional wear, adorned with gold jewelry.
Colour: Brown and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; Gold jewelry--India; Trinidad and Tobago